POLEMIK LAHIRNYA KONSEP QIRĀ‘AH SAB’AH DALAM DISIPLIN ILMU QIRĀ‘AH - Mustopa Mustopa (State Institute of Islamic Studies (IAIN) Palu, 2014)
Qirā'ah is a very important science in the study of the Ulūm al-Qur‘ān.The importance of this science lies not only on the mehod of how to recite the Qur’an but also on the method of how to understabd the meaning of the Koran. In this regard, understanding the formation of qirā‘ah history in its present form becomes important, especially because so rich treasures that the qirā‘ah possesses that appeared during the codification of official qirā'ah. The standardization of this qirâ'ah, on the one hand, gives the muslims a lot ease in reading the Koran; on the other hand, it burries the treasures of the qirā'ah science very dynamic during qirā'ah sab'ah codification. This paper discusses the crucial issues related to qirā‘ah, including the dark side of its birth to the critical and the objective reading towards the science.Kata Kunci: Aḥruf, Qirā‘ah Sab’ah, Qirā‘ah ‘Asyrah, riwayat, kodifikasi (tadwīn)